Patterns of Claims-Making on Civic Integration and Migration in Europe: Are Muslims Different? - Ruedin, Didier; Berkhout, Joost (SOM Working Papers, 2012)
Of the various immigrant and minority groups in Western Europe, Muslims are frequently singled out for their alleged cultural distance and lack of interest to participate in social and political life. Mutual distrust between Islamic organizations and political actors seems to be rising. This paper is interested in patterns of discursive interaction between Muslim groups on the one hand, and other political actors on the other hand. It examines seven European societies with varying proportions of Muslims among the population, distinct traditions of citizenship policies, and different levels of electoral success of parties voicing anti-Islam positions. Using a political claims analysis covering 1995 to 2009, we show that there are substantial differences between countries in the use of migrant-group categories. These differences do not fit the policy tradition typology suggested by Koopmans 2007, and we identify significant changes over time. Of the various groups, we find that Muslims are differentiated in the news media. The proportion of claims by Muslim organizations is nowhere in proportion to their size in the population, and indeed claims about Muslims are more common. This suggests that the construction of Muslim groups as a politically relevant category is largely done by non-Muslim political actors. The frames used in claims about Muslims differ significantly from those used for other immigrant groups. Whereas the most common frames for immigrants more generally are instrumental, for Muslims identity-based arguments are invoked more frequently. Moreover, we find that Muslims are talked about almost exclusively in connection with integration rather than immigration. This paper was presented at the Muslims and Political Participation in Britain conference in Edinburgh